Synthesis of chiral pyrene-based 1,4-dithiins [data] - Keck, Christoph; Rominger, Frank; Mastalerz, Michael (Universität, 2024)
The 1,4-dithiin motif is known for its reversible redox properties to generate radical cations and diradical dications and thus is interesting for organic electronic applications. However, examples where this motif is embedded into chiral larger fused aromatic compounds is very rare. Here we describe the syntheses of several structurally related pyrene fused dithiins and their spectroscopic investigations with a focus on tuning circular dichroism in respect the g values depending on their connectivity.
Finanziert durch: SFB 1249: N-heteropolycycles as functional materials (TP-A04)
Gesehen am 26.02.2024
Keywords: Forschungsdaten; Datenbank